Effectiveness on the Implementation of Curfew in the Municipality of Di-lasag, Aurora - Pia, Jasmin N.; Moises, Hazelle A.; Dimacuta, Nor-Ain D.; Malang, Bernandino P.; Vigonte, Florinda G. (Future Science / FSH-PH Publications, 2023)
The study identified the effectiveness of implementing curfew in the Municipality of Dilasag adopted from the Executive Order (E.O.) No. 2020-0025 s.2020 from the Provincial Government of Aurora. It was focused on the profile, the implementation of curfew regarding security, discipline, health, and crimes, and the citizens' recommendations as part of the research. The study used the descriptive research method to identify the perceptions of 359 respondents selected by Slovin's formula and systematic random sampling who had also answered the survey questionnaire. The average weighted mean revealed that curfew implementation was effective and improved the community's security, discipline, health, and crime prevention. The chi-square test as the utilized statistical treatment revealed that profile such as sex, educational attainment, and occupation has no significant difference in implementing a curfew. However, it was shown in the study that age profile has a highly significant difference in health and crime prevention and has a significant difference in security and discipline. Furthermore, the study signified that the age group was correlated to the curfew implementation, that older respondents perceived a high level of effectiveness of curfew implementation compared to younger respondents. Finally, parents' participation is an important recommendation and is still needed to improve curfew implementation in the community., and supporting political and security stability.